DYSTOCIA DUE TO STENOSIS OF VULVA IN HEIFER AND ITS SUCCESSFUL MANAGEMENT THROUGH EPISIOTOMY - KUMAR, BRIJESH KUMAR; SACHAN, VIKAS; MAURYA, S K; SONKAR, VIPIN; PAL, A S; SAXENA, ATUL (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to stenosis of vulva and its successful management through episiotomy is reported.